Experiences of resilience and its contribution to well-being among international students living in a University of Pretoria residence: a phenomenological inquiry - Ndala-Magoro, Nkateko (University of Pretoria, 2021)
Mini Dissertation (MA (Counselling Psychology))--University of Pretoria, 2021.